Hypomagnetic field effects as a potential avenue for testing the radical pair mechanism in biology - Zadeh-Haghighi, Hadi; Rishabh, Rishabh; Simon, Christoph (Frontiers in Physics, 2023)
Near-zero magnetic fields, called hypomagnetic fields, are known to impact biological phenomena, including developmental processes, the circadian system, neuronal and brain activities, DNA methylation, calcium balance in cells, and many more. However, the exact mechanism underlying such effects is still elusive, as the corresponding energies are far smaller than thermal energies. It is known that chemical reactions involving radical pairs can be magnetic field dependent at very low intensities comparable to or less than the geomagnetic field. Here, we review in detail hypomagnetic field effects from the perspective of the radical pair mechanism, pointing out that under certain conditions, they can be comparable or even stronger than the effects of increasing the magnetic field. We suggest that hypomagnetic field effects are an interesting avenue for testing the radical pair mechanism in biology.